Numerical Study of Wind Tunnel Wall Effects on Icing Cloud Distribution and Water Collection in Aero-Engine Nacelles - Cong Li; Ningli Chen; Xian Yi; Qingren Lai (Aerospace)
Icing wind tunnel tests play a critical role in evaluating ice accretion on aero-engine nacelles. However, the effects of the wind tunnel wall (WTW) on the dynamics of the icing cloud remain insufficiently quantified. This study employs an experimentally validated Eulerian–Eulerian multiphase approach to quantify WTW-induced alterations in Liquid Water Content (LWC) distribution inside the nacelle and droplet collection efficiency (β) on its surfaces. The results show that the WTW-induced flow deflection redirects droplets toward the outer nacelle surface, leading to an increase in the maximum droplet collection efficiency (βmax) and the total collected water mass on the nacelle under baseline conditions (Mach Number = 0.206) and causing a banded regime of the deviation in LWC. Parametric analysis further shows that higher inflow velocities and Median Volumetric Diameters (MVDs) enhanced the WTW’s effect on the change in LWC inside the nacelle and increased the maximum droplet collection efficiency on the nacelle’s surface. However, the increase in the intake flow rates exhibits a counteracting trend for the effect of the WTW for both the deviation in LWC and the maximum droplet collection efficiency and the total collected water mass. The findings highlight the necessity of accounting for WTW effects in icing wind tunnel testing protocols to improve flight condition extrapolation accuracy.